A model for studying the value of the inter-organisational information systems' implementation-case study: tourism industry. (24th April 2020) - Alavi, Seyedeh Nahid; Abdolvand, Neda; Harandi, Saeedeh Rajaee
The deployment of inter-organisational information systems and information sharing in the supply-chain to gain strategic benefits has become more important than ever. Although, inter-organisational information systems are essential in creating coordination between members of the supply-chain, managers are reluctant to use these systems due to the significant changes in structure, culture and business relationships. The lack of utilisation of these systems owing to environmental uncertainty in each industry, especially in the tourism industry. Hence, this study aims to examine the factors influencing the establishment of these systems. By literature review of previous studies, some factors have been derived for the development model. The results indicate that the role of environmental uncertainty is critical in achieving the benefits of inter-organisational information systems implementation. Moreover, it is suggested that implementation of inter-organisational information systems and integration of information between supply chain members has a positive impact on the overall chain performance.